The EAEU Aquaculture Market: The State, Problems and Prospects of Development - Aleksey O. Yakimovich (RUDN Journal of Economics)
Currently, fish and fish products occupy an important place in the global food market. Recently, the global volumes of caught fish and artificially grown fish have almost equaled, and the latter is showing steady growth. This trend, in the context of the catch restriction policy pursued by environmental organizations, on the one hand, and population growth, on the other, is likely to continue for the long term. For many countries, fish plays an important role in solving the food problem. The demand for fish and fish products is growing in the member States of the Eurasian Economic Union (EAEU), which have sufficient potential for the development of fisheries based on the available resource potential and deepening interstate cooperation. One of the promising areas of integration cooperation within the framework of a coordinated agro-industrial policy is cooperation in the field of aquaculture. In the EAEU member states, the development of aquaculture is becoming one of the priority state tasks in the field of agro-industrial complex. At the same time, in order to increase such production, it is necessary to create appropriate conditions, form measures and mechanisms of state support, taking into account the projected results of its implementation. The article provides a general description of the production potential of aquaculture cultivation in the EAEU. The paper presents the activities of the Eurasian Aquaculture Alliance, an association aimed at supporting the development of aquaculture production; its cooperation with the Eurasian Economic Commission is considered. The most acute problems and promising areas of fish farming development in the Eurasian space are highlighted.